2014
DOI: 10.1016/j.micromeso.2013.12.004
|View full text |Cite
|
Sign up to set email alerts
|

A new route of synthesis of Na-Mica-4 from sodalite

Abstract: Synthesis of Na-Mica-4 has been achieved by a "mix and calcine" 14 method using sodalite and magnesium fluoride as the only precursors. Previous research 15 found sodalite as a key intermediate reaction product in the formation of Na-Mica-4 16 when the NaCl melt method was employed. Similarities in structure, chemical 17 composition and cation distribution in products using the proposed method and the 18 NaCl melt method are described and suggest that Na-Mica-4 is a very stable product. 19The use of sodalite a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 22 publications
4
8
0
Order By: Relevance
“…The excess of NaOH used in the synthesis tends to cause aggregation, as seen by the highest particle diameter values obtained for the sample S7, resulting from the interaction between the Na + ions and the negative charges of SOD framework. Thus, SOD showed the highest polidispersity index due to its aggregative behavior [33].…”
Section: Direct Synthesis Of Zeolites 12mentioning
confidence: 99%
See 1 more Smart Citation
“…The excess of NaOH used in the synthesis tends to cause aggregation, as seen by the highest particle diameter values obtained for the sample S7, resulting from the interaction between the Na + ions and the negative charges of SOD framework. Thus, SOD showed the highest polidispersity index due to its aggregative behavior [33].…”
Section: Direct Synthesis Of Zeolites 12mentioning
confidence: 99%
“…The particle size distribution (parameters d 10 , d 50 and d 90 ) was measured by laser diffraction (Mastersizer 2000, Malvern) using aqueous suspensions of the samples (0.001 g/mL) sonicated in ultrasounds prior to the measurements. The polydispersity index (PI) was calculated according to Naranjo et al[33]. Zeta potential (ZP) was determined by a laser doppler electrophoresis analyzer (ZetaSizer Nano, Malvern) using 0.005 g of sample in 100 mL of aqueous dispersion at 25 °C.The cation-exchange capacity (CEC) of the zeolites was determined by NH 4 + ion exchange method with a 1M NH 4 Cl solution (pH ∼7).…”
mentioning
confidence: 99%
“…9 In many cases, solid state synthesis procedures have been used to prepare these materials 10 and fluoride ions have been employed to aid mineralization [6,7,8]. Procedures for synthe-11 sizing fine Na-Mica-4 have been refined over a period of time and many starting materials 12 have been tested to achieve the same final product [2,3,9,10,11,12]. Cost effectiveness is 13 one of the main driving forces behind all those attempts.…”
mentioning
confidence: 99%
“…Alba et al (Alba et al, 2006) have synthetized a new family of clay minerals that has been demonstrated to be attractive adsorbents. These synthetic fluorophlogopites have layer charge in the range of the brittle micas but unlike the natural ones, they exhibit swelling properties and cation exchange capacity (Naranjo et al, 2014). Those as-made micas, Na-Mn (n is the layer charge which derives from the tetrahedral Si +4 /Al +3 substitutions and can be found between 2 and 4), have exhibited excellent capacity for the removal of radioactive cations and organic pollutants from wastewater (Alba et al, 2006;García-Jiménez et al, 2016;Osuna et al, 2019bOsuna et al, , 2018Pazos et al, 2017) and are promising materials for heavy metal removal, although their efficiency has not been proven yet.…”
Section: Introductionmentioning
confidence: 99%